Fungsi Sosial Bahasa dalam Aktivitas Komunikasi Keagamaan Formal - Amelia Dewi; Marlina; Nur kholidah; Reski Hidayah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Arabic is frequently used in official religious activities; however, its social functions have not been widely examined from a sociolinguistic perspective. This study aims to analyze the social functions of Arabic in formal religious activities at the Office of the Ministry of Religious Affairs of Mandailing Natal Regency using a sociolinguistic approach. This research employs a qualitative descriptive method, with data collected through observations of formal religious activities, analysis of institutional documents, and interviews with relevant informants. Data analysis is conducted based on the concepts of language domains and social functions of language within sociolinguistic studies. The findings reveal that Arabic functions as a religious symbol that reinforces a sacred atmosphere, strengthens the Islamic identity of the institution, and provides religious legitimacy to formal activities. In addition, the use of Arabic contributes to the construction of religious authority, even though not all participants fully understand the linguistic meanings of the utterances. These findings indicate that Arabic in the context of religious bureaucracy carries significant social and institutional meanings beyond its communicative function. This study is expected to contribute to sociolinguistic studies on religion and to enhance understanding of the role of Arabic in formal religious settings in Indonesia.